Altered DNA methylation patterns of the H19 differentially methylated region and the DAZL gene promoter are associated with defective human sperm. - Bo Li (PLoS ONE, 2013)
DNA methylation disturbance is associated with defective human sperm. However, oligozoospermia (OZ) and asthenozoospermia (AZ) usually present together, and the relationship between the single-phenotype defects in human sperm and DNA methylation is poorly understood. In this study, 20 infertile OZ patients and 20 infertile AZ patients were compared with 20 fertile normozoospermic men. Bisulfate-specific PCR was used to analyze DNA methylation of the H19-DMR and the DAZL promoter in these subjects. A similar DNA methylation pattern of the H19-DMR was detected in AZ and NZ(control), with only complete methylation and mild hypomethylation(<50% unmethylated CpGs) identified, and there was no significant difference in the occurrence of these two methylation patterns between AZ and NZ (P>0.05). However, the methylation pattern of severe hypomethylation (>50% unmethylated CpGs ) and complete unmethylation was only detected in 5 OZ patients, and the occurrence of these two methylation patterns was 8.54±10.86% and 9±6.06%, respectively. Loss of DNA methylation of the H19-DMR in the OZ patients was found to mainly occur in CTCF-binding site 6, with occurrence of 18.15±14.71%, which was much higher than that in patients with NZ (0.84±2.05%) and AZ (0.58±1.77%) (P<0.001).Additional, our data indicated the occurrence of >20% methylated clones in the DAZL promoter only in infertile patients, there was no significant difference between the AZ and OZ patients in the proportion of moderately-to-severely hypermethylated clones (p>0.05). In all cases, global sperm genome methylation analyses, using LINE1 transposon as the indicator, showed that dysregulation of DNA methylation is specifically associated with the H19-DMR and DAZL promoter. Therefore, abnormal DNA methylation status of H19-DMR, especially at the CTCF-binding site 6, is closely associated with OZ. Abnormal DNA methylation of the DAZL promoter might represent an epigenetic marker of male infertility.